Consumer and retailer perceptions of market transactions and the complaining consumer - G. G. Rousseau (SA Journal of Industrial Psychology, 1987)
The purpose of the study is to compare consumers' and retailers' perceptions of actions taken in particular types of buying situations. Hypotheses relating to differences existing between the perceptions of consumers and retailers of actions taken in the buying situation are proposed and empirically tested using data from a systematic random sample of 150 consumers and 47 retailers in the Port Elizabeth metropolitan area. Complaints about products recently bought by subjects in tjhe sample were also analysed as part of the study. Results imply that perceptual differences occurred in five of the fourteen situations portrayed, indicating possible causes of consumer frustration. Complaints analysed through the survey identified inadequate after-sales service, defective or malfunctioning products, and perishable food items as main sources of dissatisfaction. Opsomming Die doel van hierdie studie is om verbruikers en kleinhandelaars se waarnemings van optrede in spesifieke koopsituasies te vergelyk. 'n Hipotese dat verskille wel bestaan tussen die waarnemings van verbruikers en kleinhandelaars ten opsigte van optrede binne die koopsituasie, word gestel en empirics getoets. Data is verkry d.m.v. 'n sis- tematiese ewekansige steekproef met 150 verbruikers en 47 kleinhandelaars in die Port Elizabeth metropolitaanse gebied. Klagtes oor produkte onlangs aangekoop deur proefpersone in die steekproef is verder ontleed as deel van die studie. Resultate impliseer dat waamemingsverskille voorkom in vyf van die veertien situasies uitgebeeld wat moontlike oorsake van frustrasies aandui. Klagtes ontleed deur die opname het ontoereikende na-verkope diens, foutiewe produkte en bederfbare voedselitems as hoofbronne van ontevredenheid geidentifiseer.